Spokane's legendary Davenport Hotel [videorecording (VHS)] - Briley, Bob; Bolser, Jim; Briley, Robin; Bamonte, Tony 1942-; Bamonte, Suzanne (Peak Video Productions, 2002)
A visual history of "Spokane's legendary Davenport Hotel" from its opening in 1914, through its sale to a succession of owners and unfortunate decline, to its restoration beginning in 2000.